Poor sleep is associated with lower physical activity in a population-based cohort of middle-aged and older adults - Susanna C. Larsson; Emma Hållström; Karl Michaëlsson; Olga E. Titova (Scientific Reports)
Abstract Sleep problems and inadequate physical activity (PA) are associated with numerous adverse health outcomes. Most studies explored the influence of PA on sleep, but how sleep affects engagement in PA across adulthood remains less well investigated. This study examined the association between sleep traits and PA reported the following year in 51,247 Swedish women and men (55–93 years), who completed questionnaires regarding their sleep, PA, and other characteristics. Health status was assessed with data from the Swedish National Patient Registry. Odds ratios and 95% confidence intervals were estimated by binary logistic regression. In multivariable analysis, long sleep duration (≥ 9 h/night), sleep disturbance, and symptoms of sleep-disordered breathing (SDB) were associated with lower odds of engaging in walking or cycling, and exercising the following year. In addition, short sleep duration (< 7 h/night), sleep disturbance, and symptoms of SDB were linked to sedentary behavior (time spent on reading or watching TV). Several sex- and age-specific associations were observed. In addition to previous evidence of a positive effect of PA on sleep, our findings indicate that poor sleep may contribute to lower engagement in PA and a higher level of sedentary behavior, highlighting the bidirectional nature of the relationship between PA and sleep.